Previously Neglected Effects of Strong Horizontal Winds on Raindrop Collisions in Tropical Cyclones - Lin Deng; Xuwei Bao; Istvan Geresdi; Lulin Xue; Wei Huang; Yang Zhao; Wanchen Wu; Tiantian Li (Geophysical Research Letters)
Abstract Persistent strong winds are a common feature within the near‐surface layer of tropical cyclones, which can induce pronounced horizontal motion as raindrops descend. However, current state‐of‐art microphysics schemes typically only consider the vertical motion of raindrops, ultimately failing to accurately simulate the collisional outcomes of raindrops and the associated raindrop size distributions (RSDs) under strong winds. For instance, the original bin microphysics scheme was unable to successfully reproduced the evolution of RSDs with decreasing height, as measured from the multi‐layer observations during the landfall of Typhoon Pakhar (2017). Thus, this study introduces a modified bin microphysics scheme that incorporates the influence of horizontal wind speeds, vertical wind shear and smaller‐scale turbulence on the total movement velocity (including horizontal and vertical components) of raindrops, and consequently on their collisional outcomes. This modification demonstrates a remarkable improvement in the representation of the intrinsic variation in RSDs with decreasing height under strong‐wind conditions.